2003
DOI: 10.1097/01.hdx.0000074437.07268.00
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Ethnicity, and Genes in Cardiovascular Disease.

Abstract: Women are underrepresented in clinical trials. Lower doses of beta-blockers are required for Southeast Asians. ACE and ARB's are teratogenic in the second trimester. Torsades de Pointes is more common in women related to a longer QT-interval. Lower dose OCPs decrease the risk of MI, stroke and thrombosis. HRTs are not effective for CAD prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…The high susceptibility of this Argentine and Uruguayan population to show MI at the evening points out to the relevance of variations in the spectrum of cardiovascular disease between different regions of the world and ethnic groups [ 21 - 25 ]. Indeed, it has been suggested that environmental-genetic background, socio-economic, and customs could underlie ethnic disparities in cardiovascular risk factor profiles [ 30 , 31 ]. A recent study confirms the existence of ethnic disparities in cardiovascular risk prevalence [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high susceptibility of this Argentine and Uruguayan population to show MI at the evening points out to the relevance of variations in the spectrum of cardiovascular disease between different regions of the world and ethnic groups [ 21 - 25 ]. Indeed, it has been suggested that environmental-genetic background, socio-economic, and customs could underlie ethnic disparities in cardiovascular risk factor profiles [ 30 , 31 ]. A recent study confirms the existence of ethnic disparities in cardiovascular risk prevalence [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, past trials for CAD management in women have included the use of hormone replacement therapy (HRT). This treatment strategy is no longer in practice owing to studies that demonstrated increased risk of adverse cardiac events in women on HRT [15].…”
Section: Noninvasive Management Of Coronary Artery Diseasementioning
confidence: 97%
“…Discordant results were reported so far on the role of such variants as risk factors for venous thrombosis, mainly because: i) heterogeneous criteria have been used so far to select the patients; ii) most studies pooled male and female patients and women are frequently underrepresented [10] thus obscuring eventual sex differences [7,11]; iii) some studies compared the frequency of prothrombotic gene variants in patients and controls of different geographical areas. Finally, as regards the clinical context, the ordering of tests for thrombophilia is strongly heterogeneous [12] and scarcerly respective of guidelines [13].…”
Section: Introductionmentioning
confidence: 99%